Building MSMEs Marketing Performance through Innovation during the Covid-19 Pandemic - Muji Gunarto; Anggun Yolandia Monica Jaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Market globalization has implications for MSME actors who have to compete in terms of marketing innovation. The development of technology that is integrated with trade moves so rapidly that it gave birth to the industrial revolution 4.0. There are MSME actors who still rely on conventional methods to run their business. If MSME actors do not want to innovate, there will be an impact that causes business to be disrupted. With the COVID-19 pandemic in 2020 until now, the economy in Indonesia has been affected in all fields. With the increase in the number of MSMEs, their competitiveness will also increase, to win market share, various innovations are needed, especially marketing innovations. The purpose of this research is to analyze and prove the influence of innovation on marketing performance. This study uses a quantitative approach with a survey of MSME actors in the culinary field in Palembang City as many as 100 respondents from a population of 45,827 thousand MSME actors. The data in this study were obtained by direct questionnaires to SMEs in the culinary field. Data processing is done by using Structural Equation Modeling (SEM). The data collection technique used the Random Sampling method. The results showed that there was a positive and significant influence between innovation on marketing performance. The implications of this research can be useful for MSME actors in the city of Palembang so that they can partner to improve their ability to innovate so that MSMEs can advance to class and be able to overcome the various negative impacts of the Covid-19 pandemic which has an impact on MSME marketing performance.